KESADARAN BERZAKAT DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KABUPATEN TAKALAR - Baharuddin, Baharuddin; Siradjuddin, Siradjuddin; Rahman, Danial; Arif, Widyantono (Idaarah: Jurnal Manajemen Pendidikan, 2023)
The aim of this research is to describe awareness of zakat in improving community welfare (overview of motivation and distribution of zakat) in Takalar Regency. This research uses field research with a qualitative approach. The data collection techniques used were observation and interviews. Data processing and analysis techniques go through the stages of data reduction, data presentation, and drawing conclusions. The results of the research conducted show that: (1) the people in Takalar Regency do not yet have full awareness of zakat due to their still minimal understanding of the obligation to zakat other than zakat fitrah so the government is working with Baznas to socialize to the public about the importance of delivering zakat to those classified in the muzakki category ; (2) the motivation to give zakat to the community in Takalar Regency is influenced by their level of welfare because in recent years, the level of community welfare in Takalar Regency has decreased due to the Covid-19 pandemic; (3) zakat collected in Takalar Regency is distributed in several forms, such as assistance with education costs, assistance with school uniforms, cash assistance, and assistance in the form of business capital to underprivileged but still productive people; and 4) the distribution of zakat carried out in Takalar Regency has an impact on community motivation after experiencing the benefits of the zakat funds that have been distributed. This gives rise to public trust in zakat managers, thus increasing their awareness in distributing their zakat to UPZ to be managed by Baznas and then distributed to people who are classified as mustahik.